2002
DOI: 10.1530/eje.0.1470597
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous mutation within the conserved Ala-Phe-Asn-Glu-Thr motif of exon 7 of the LH receptor causes male pseudohermaphroditism

Abstract: Background: Human chorionic gonadotropin/luteinizing hormone (hCG/LH) function in the male is mediated by the LH receptor (LHR) and is crucial for the normal development of internal and external genitalia. We report a 46, XY patient who presented at the age of 16 with a female phenotype and delayed puberty. Gonads were located bilaterally in the inguinal canal, removed surgically and showed hypoplastic Leydig cells. Immunostaining for the LHR revealed that some Leydig cell progenitors were positive, while othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…Furthermore, the β-strands of LHCGR LRR 3 and 6 were identified as hCG/LH-selective determinants (Song et al, 2001a;Song et al, 2001b). In fact, Gromoll et al ( Gromoll et al, 2007) reported a homozygous p.Phe194Val mutation in a case of LCH, which further supports the conclusion of the AFNGT region encoded by the sequence of exon 7 as being crucial for receptor function. Collectively, these data suggest that the LHCGR lacking exon 7 caused by a mutation in the 3' splice site of intron 6 abolishes the function of the LHCGR gene.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, the β-strands of LHCGR LRR 3 and 6 were identified as hCG/LH-selective determinants (Song et al, 2001a;Song et al, 2001b). In fact, Gromoll et al ( Gromoll et al, 2007) reported a homozygous p.Phe194Val mutation in a case of LCH, which further supports the conclusion of the AFNGT region encoded by the sequence of exon 7 as being crucial for receptor function. Collectively, these data suggest that the LHCGR lacking exon 7 caused by a mutation in the 3' splice site of intron 6 abolishes the function of the LHCGR gene.…”
Section: Discussionmentioning
confidence: 61%
“…Among them, p. Val144Phe and p.Phe194Val were observed to interfere with membrane insertion of the receptor (Richter-Unruh et al, 2004;Gromoll et al, 2007), while p.Ile114Phe in the LRR3 resulted in reduced ligand binding and signal transduction of the receptor, with less effect on membrane insertion of the receptor (Leung et al, 2006). The mutation of p. Ile152Thr located in the LRR5 was demonstrated to abolish the binding of the hormone and signal transduction activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information condensed as follows: rhodopsin (Stojanovic and Hwa, 2002;Mendes et al, 2005;Tao, 2006); V2R (Bernier et al, 2004a,b;Fujiwara and Bichet, 2005;Bichet, 2006;Boson et al, 2006;Robben and Deen, 2007;Robben et al, 2006); GnRHR (Beranova et al, 2001;Janovick et al, 2003a;Ulloa-Aguirre et al, 2004a,b); CaR (Brown, 2007;Huang and Breitwieser, 2007); LHR (Gromoll et al, 2002;Martens et al, 2002;Huhtaniemi and Themmen, 2005;Piersma et al, 2007); FSHR (Rannikko et al, 2002;Meduri et al, 2003;Huhtaniemi and Themmen, 2005); TSHR (Biebermann et al, 1997;Costagliola et al, 1999;Tonacchera et al, 2000Tonacchera et al, , 2004Calebiro et al, 2005;Davies et al, 2005); E-BR (Tanaka et al, 1998;Fuchs et al, 2001;Chen et al, 2006;Tao, 2006); MC1R-4R (Beaumont et al, 2005;Clark et al, 2005;Govaerts et al, 2005;Tao, 2005Tao, , 2006Farooqi and O´Rahilly, 2006;Hinney et al, 2006;Lubrano-Berthelier et al, 2006;Alharbi et al, 2007;Lin et al, 2007); and CCR5 receptor (Lede...…”
Section: Of-function Diseases or Abnormalities Caused By Particular Gmentioning
confidence: 99%
“…There are other GPCRs in which mutations provoke loss of function of the receptor because of intracellular retention of the abnormal (and presumably misfolded and/or incompletely processed) receptor and, consequently, decreased or absent cell surface membrane expression. Some trafficking defective mutants of the glycoprotein hormone receptors [lutropin (LH), follitropin (FSH), and thyrotropin receptors] have been described in patients with Leydig cell hypoplasia, a rare autosomal recessive form of male pseudohermaphroditism (LH receptor) (Gromoll et al, 2002;Martens et al, 2002), in women with ovarian dysgenesis (FSH receptor) (Rannikko et al, 2002;Meduri et al, 2003), and in congenital hypothyroidism (thyrotropin receptor) (Biebermann et al, 1997;Costagliola et al, 1999;Tonacchera et al, 2000Tonacchera et al, , 2004. Loss-of-function mutations in the calcium-sensing receptor due to intracellular retention of the mutant receptor have been found in patients with familial hypocalciuric hypercalcemia (D'Souza-Li et al, 2002).…”
Section: Introductionmentioning
confidence: 99%